A wide bandgap conjugated polymer donor based on alkoxyl-fluorophenyl substituted benzodithiophene for high performance non-fullerene polymer solar cells. Issue 3 (2nd January 2019) - Li, Wanbin; Li, Guangda; Guo, Huan; Guo, Xia; Guo, Bing; Zhu, Qinglian; Fan, Qunping; Ma, Wei; Zhang, Maojie; Li, Yongfang
Abstract : Through side chain fluorination strategy, the PCE was improved from 6.2% for POPB-based device to 11.7% for PFOPB-based device. Abstract : A new wide bandgap (WBG) conjugated polymerPFOPB based on a fluorinated-alkoxyphenyl benzodithiophene donor unit and a benzodithiophene-4, 8-dione acceptor unit was designed and synthesized for application as a donor in non-fullerene (NF) polymer solar cells (PSCs). In order to investigate the effect of side chain fluorination on the photovoltaic performance, a corresponding non-fluorinated polymerPOPB was also synthesized as a comparison material. Compared toPOPB with a bandgap of 1.81 eV, a highest occupied molecular orbital (HOMO) energy level of −5.38 eV, an extinction coefficient of 5.31 × 10 4 cm −1 at 577 nm and a hole mobility of 3.96 × 10 −4 cm 2 V −1 s −1, the fluorinated polymerPFOPB possesses a wider bandgap of 1.86 eV, a deeper HOMO level of −5.50 eV, a higher extinction coefficient of 8.45 × 10 4 cm −1 at 612 nm and a higher hole mobility of 1.51 × 10 −3 cm 2 V −1 s −1 . ThePFOPB :IT-4F-based PSCs exhibit a much higher power conversion efficiency (PCE) of 11.7% thanPOPB :IT-4F-based devices (6.2%). These results suggest that side-chain fluorination is an effective strategy to improve the optoelectronic properties of WBG polymers in NF-PSCs.